Defining corporate energy policy and strategy to achieve carbon emissions reduction targets via energy management in non-energy intensive multi-site manufacturing organisations. (15th May 2018) - Finnerty, Noel; Sterling, Raymond; Contreras, Sergio; Coakley, Daniel; Keane, Marcus M.
Abstract: Research on the characteristics of long-term energy policy and associated strategies in multi-site manufacturing organisations is limited. Non-energy intensive multinationals do not face the environmental regulations required by their energy intensive counterparts, leading to missed opportunities and further widening the energy efficiency gap. This work investigates the development of along-term energy policy and supporting strategy to close the energy efficiency gap focused on the inherent barriers found for non-energy intensive multi-site organisations. A systematic literature review identifies the essential components and the associated barriers/drivers to energy management. Highlights include (i) a review of energy policy guidelines and standards, (ii) an analysis of the decision-making practices, (iii) the influence of the non-energy benefits of energy-related investments and (iv) a study of six leading sustainable global organisations to identify best energy management practices. Subsequently, this work proposes a methodology to formulate a 'corporate energy policy and an associated strategy' in support of non-energy intensive multi-national manufacturing organisations by focusing on their specific characteristics and barriers. A case study is presented with findings on initial deployment in a Fortune 500 multinational corporation. Finally, conclusions are drawn and future work is proposed.